Diagnostic value of bone scintigraphy versus cardiovascular magnetic resonance in cardiac amyloidosis - Josefin Obergassel; Michael Bietenbeck; Nuriye Akyol; Volker Vehof; Claudia Meier; Maria Theofanidou; Philipp Stalling; Ali Yilmaz (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Accurate diagnosis of transthyretin amyloidosis cardiomyopathy (ATTR-CM) and its differentiation from light-chain (AL) cardiac amyloidosis (CA) cases (AL-CM) are of paramount importance. Surprisingly, comparative imaging data based on concurrent cardiovascular magnetic resonance (CMR) and bone scintigraphy in the same patients with biopsy-proven diagnosis of CA are still rare. Methods: This was a real-world retrospective single-center study based on a local clinical care pipeline and we carefully analyzed clinical, laboratory, CMR, and bone scintigraphy data (and if necessary additional endomyocardial biopsy [EMB] data) in patients with suspected CA. As a major inclusion criterion, we only looked at those patients who underwent both a CMR study and a bone scintigraphy—with a clear-cut imaging finding detected by at least one imaging method. Results: One hundred twenty three patients in whom the final diagnosis was obtained either non-invasively based on combined findings from bone scintigraphy and monoclonal protein studies or invasively based on additional EMB findings were included. A positive CMR result indicating the presence of CA was found in 121 patients—suggesting a CMR sensitivity of 98.4% for the diagnosis of any CA. Bone scintigraphy identified 18 patients with low to moderate uptake (Perugini score = 0–1) and 105 patients with high uptake (Perugini score ≥2)—resulting in a sensitivity for bone scintigraphy of 85.4% for the diagnosis of any CA. There was an agreement (“diagnostic match”) between CMR and bone scintigraphy results in 103 patients (84%) of the total study cohort, while a discrepancy (“diagnostic mismatch”) was observed in 20 patients (16%). In 18 out of these 20 diagnostic mismatch cases, CMR correctly diagnosed the presence of CA despite a negative or inconclusive result on bone scintigraphy (8 with AL-CM, 8 with ATTR-CM, and 2 with EMB-proven but unspecified CA). Conclusion: CMR shows a substantially higher diagnostic yield for the diagnosis of CA compared to bone scintigraphy, if a real-world cohort of patients comprising different subtypes of CA is looked at, since CMR does not only detect ATTR-CM but also depicts other CA subtypes such as AL. In case of a clear-cut positive CMR result unequivocally indicative of CA, there is no incremental diagnostic value of an additionally performed bone scintigraphy.